Corticosteroids in Duchenne muscular dystrophy: impact on the motor function measure sensitivity to change and implications for clinical trials. (9th October 2017) - Schreiber, Audrey; Brochard, Sylvain; Rippert, Pascal; Fontaine‐Carbonnel, Stephanie; Payan, Christine; Poirot, Isabelle; Hamroun, Dalil; Vuillerot, Carole
Abstract : Aim: To monitor the evolution of the motor function of ambulatory patients with Duchenne muscular dystrophy (DMD) treated by corticosteroids for 2 years in comparison with untreated patients. Method: This observational, multicentre cohort study explores the evolution of the motor function measure (MFM) over a 24‐month period for 29 ambulant corticosteroids‐treated and 45 ambulant untreated patients with DMD. Results: Significant differences were found between mean MFM scores in corticosteroids‐treated and untreated groups for domain 1 of the MFM (standing position and transfers; D1), domain 2 of the MFM (axial and proximal motor function; D2), and domain 3 of the MFM (distal motor function; D3). Subscores were between 0 months and 6 months, and 0 months and 24 months. For the D1 subscore specifically, there was a significant increase in the corticosteroids‐treated group (mean±standard deviation [SD] slope of change=12.6±15.5%/y), while a decrease was observed in the untreated group (−17.8±17.7%/y) between 0 months and 6 months ( p <0.001). Sensitivity to change as assessed by standardized response means was high between 12 months and 24 months for D1 of both corticosteroids‐treated and untreated groups (1.0 and 1.2 respectively), and low for D2 and D3 of both treated and untreated groups. Interpretation: Patients with DMD treated by corticosteroids present a different course of the disease as assessed by MFM, confirming the sensitivity to change of the MFM in this population. What this paper adds: Corticosteroids have a quantitative impact on muscle strength 6 to 24 months after starting treatment. Motor function measure is a valid outcome measure in Duchenne muscular dystrophy patients under corticosteroid treatment. What this paper adds: Corticosteroids have a quantitative impact on muscle strength 6 to 24 months after starting treatment. Motor function measure is a valid outcome measure in Duchenne muscular dystrophy patients under corticosteroid treatment. This article is commented on by Domingos and Muntoni on page117 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. Video Podcast:https://www.youtube.com/watch?v=qNmTSgJiJco